SOUTH AFRICAN INTELLIGENCE OVERSIGHT AND THE INTERCEPTION OF COMMUNICATION - Thebus, Donovan Farrel (My University, 2012)
South African Intelligence services have made significant strides in conforming to civilian led control. Albeit, from numerous media reports and articles, and in an official Ministerial Intelligence Review Commission Report (for the period 2006 to 2009), acute problems within the intelligence services and intelligence oversight became evident. The interception of communication by the intelligence services appeared to be unregulated, unlawfully and inconsistent with the constitution. Furthermore, intelligence oversight appeared to be functioning in a reactive manner. This research report explores and explains the role of intelligence oversight in relation to the interception of communication. It concludes by recommending that intelligence oversight be institutionalised under chapter 9 of the constitution
MM thesis - P&DM
Keywords: Intelligence services; Interception of communication